(untitled) (Malaysian Journal of Civil Engineering, 2018)
This paper presents some experimental results and discusses the used of timber clinker as partial aggregate replacement in producing concrete. A number of tests were conducted to identify the physical properties of timber clinker aggregate such as density, aggregate impact value (AIV) test and aggregate crushing value (ACV) test, slump, X-Ray Fluorescence (XRF) test and compressive strength of timber clinker aggregate concrete. Two series of concrete mixes with Supracoat SP1000(C0, C10, C20, C30) and without Supracoat SP1000(CA0, CA10, CA20, CA30) with various percentage of 0%, 10%, 20% and 30% 10 mm sieve size timber clinker aggregate used as partial replacement in producing concrete. A total of forty 150 x 150 x 150 mm cubes samples were prepared for both series of concrete mixes and tested at 7, 14 and 28 days of water curing. The results obtained showed that timber clinker aggregate concrete gained highest compressive strength for both series of concrete mixes C20 and CA20 which was 37 MPa and 34 MPa respectively. The optimum percentage used of timber clinker aggregate in producing concrete was 20% where if exceeded will decreased the compressive strength and Supracoat SP1000 added tend to improve the concrete slump. The physical properties test indicated the contribution to the concrete strength development. The results obtained and observation made in this study suggest that timber clinker aggregate successfully used as partial replacement in producing concrete and performed better strength development